Oral health-related quality of life in patients with oral squamous cell carcinoma: A case-control study - Zahra Ghorbani; Soheila Manifar; Ghazaleh Bohloli; Arezoo Aghakouchakzadeh; Ahmadreza Mirzaei (Wolters Kluwer Medknow Publications, 2023)
Background: The prevalence of oral squamous cell carcinoma (OSCC) has increased in recent years. With the development of various treatments, the mortality rate has decreased and more people are living with the consequences of the disease and its treatment, which can have a great impact on the quality of life. Some questionnaires measure the impact of the disease on daily activities and patient behavior. In this study, the oral health-related quality of life (OHRQOL) was assessed through the Oral Health Impact Profile (OHIP)-14 questionnaire between the OSCC patient and control groups. Materials and Methods: In this cross-sectional study, the OHIP-14 questionnaire was given to 51 OSCC patients who had completed the treatment at least 6 months before participating in this study and 51 healthy individuals, and we used the Chi-square test, independent sample t-test, one-way ANOVA, and linear regression in three models. P = 0.05 was considered statistically significant. Results: The mean age of patients was 55.86 ± 15.04 years and the control group was 54.96 ± 14.08 years. Women made up 51% of patients. The mean OHIP score was 22.84 ± 11.42 in the patient group and 17.92 ± 9.23 in the control group, which indicates a significant (P = 0.005) difference between the two groups according to the independent sample t-test. Conclusion: The OHRQOL of patients has significantly decreased compared to the control group. Surgery had the lowest quality reduction, and combined surgical treatment with radiotherapy and chemotherapy had the highest reduction in the OHRQOL. It is recommended to have regular follow-up sessions and to have a proper diet during and after treatment.